Question

Find the general solution of the differential equation

y′′ − 2y′ − 3y = ae3t, where a is a constant

Answer #1

Find the general solution of the following differential
equation:
y^4 - 3y''' + 3y'' - 3y' + 2y = 0

Find the general solution of the differential equation:
y''' - 3y'' + 3y' - y = e^x - x + 16
y' being the first derivative of y(x), y'' being the second
derivative, etc.

Find the general solution of the equation.
y''-3y'+2y=e^3t

Find the general solution to the differential equation
2y'+y=3x

a) Find the general solution of the differential equation
y''-2y'+y=0
b) Use the method of variation of parameters to find the general
solution of the differential equation y''-2y'+y=2e^t/t^3

find the general solution of the differential equation:
y''+2y'+4y=xcos3x

Find the general solution of the differential equation
y′′−3y′−40y=84e^(2t).

Find the general solution of the given differential
equation.
y'' − y' − 2y = −8t + 6t2
y(t) =

Find the general solution of the differential equation: y' + 2y
= 2sin (4t) Use lower case c for the constant in your answer.

find the general solution of the differential equation: y' + 2y
= te^−4t. Use lower case c for the constant in your answer.
y(t) = _________________

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 14 minutes ago

asked 24 minutes ago

asked 29 minutes ago

asked 30 minutes ago

asked 31 minutes ago

asked 53 minutes ago

asked 57 minutes ago

asked 58 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago